The Relationship between Workload and Teachers Effectiveness in Secondary Schools: A Case of Uganda - Nuwaha, Wilber; Atukunda, Gershom; Kyayemagye, Florah (East African Journal of Education Studies, 2023)
he study assessed the relationship between teachers’ workload and their effectiveness in secondary schools. A descriptive survey design was adopted for this study to determine the frequency of occurrences of the phenomenon and discover whether or not there is a relationship that exists between the variables. The target population of this study comprised Headteachers, Deputy Headteachers, Directors of Studies, and class teachers in the selected Secondary Schools in Sheema Municipality, Sheema Municipality. The study employed a questionnaire and interviews. The study used Pearson correlation to determine the level of statistical relationship between workload and teachers’ effectiveness. Results indicate that there is a weak but significant positive correlation between teachers’ workload and their effectiveness in secondary schools (r=0.012, p<0.045). It was found that teachers are always prepared when holding classes. It was concluded that teachers in secondary schools of Sheema Municipality are given other responsibilities apart from teaching. These include; duty supervision, monitoring, some co-curricular activities like drama, football guidance, and counselling. It was also concluded that teachers in secondary schools of Sheema Municipality are effective in terms of students’ improvement in discipline and good performance registered in terms of academics. It was also concluded that more workload for teachers affects their effectiveness negatively, that is, failure to prepare schemes of work, and lesson plans, assess learners, maintain discipline, and participate in co-curricular activities. The study recommends that the government should set more innovative guidelines for teacher workload in schools to enable school administrators not to overload the teachers, which may result in ineffectiveness.